Mesenchymal stem cells alleviate experimental rheumatoid arthritis through microRNA-regulated IκB expression - Xin Yan; Yurong Cen; Qin Wang (2016)
Abstract Previous studies have demonstrated that mesenchymal stem cell (MSC) transplantation reduces the severity of collagen-induced arthritis (CIA) in mice, which is a model for rheumatoid arthritis (RA) in humans. However, the underlying molecular mechanisms remain ill-defined. Here, we showed that MSC transplantation reduced the activities of NF-κB signaling and decreased microRNA-548e (miR-548e) levels in the joint tissue in CIA-mice, seemingly through activation of transforming growth factor β receptor signaling. Bioinformatics analyses revealed that miR-548e inhibited protein translation of the NF-κB inhibitor, IκB, through binding to the 3′-UTR of the IκB mRNA. MSCs co-transplanted with adeno-associated virus (AAV) carrying miR-548e abolished the therapeutic effects of MSCs on CIA. On the other hand, transplantation of AAV carrying antisense of miR-548e (as-miR-548e) partially mimicked the effects of MSC transplantation on CIA. Together, these data suggest that MSC transplantation may alleviate experimental RA partially through suppressing miR-548e-mediated IκB inhibition.